Implementation of Sharia Payment Accounting Treatment (RAHN) - Karmila, Yusri; Muin, Rahmawati; Abdullah, Wahyuddin; Supatminingsih, Tuti (IAIN Batusangkar, 2024)
This study aims to find out whether the application of sharia pawn accounting in several sharia pawnshop companies is in accordance with PSAK 107 and the Fatwa of the National Sharia Council. This study uses a descriptive qualitative method. The data was obtained through in-depth interviews with related parties, such as Pegadaian Syariah financial managers and staff, as well as through the study of relevant internal and external documents. As a result of the research, it can be concluded that the implementation of rahn in Makassar Sharia Pawnshops has supported the principles of transparency and justice in accordance with sharia values. However, the study also found several challenges in implementation, such as a lack of understanding of the details of Sharia accounting standards on the part of staff and the need for ongoing training to improve compliance with Sharia accounting standards.